Association of Metabolic Factors with Essential Hypertension (TAJ: Journal of Teachers Association, 2011)
Background-Metabolic syndrome is a risk factor for cardiovascular disease, so it should call attention. South Asian person has preponderance to it.Objectives-The proper findings of metabolic syndrome are a key to prevent cardiovascular disease. Hypertension is a component of metabolic syndrome with which patients are at increased risk for cardiovascular disease.Methods-This study was carried out in cardiology outdoor of Shaheed Suhrawardy medical college hospital, Dhaka. A total of 322 patients were enrolled from January 2008 to December 2010. Metabolic syndrome was defined as three of the followings: (a) Abnormal fasting serum level of glucose (≥110 mg/dl or 6.1 mmol/L), ( b) abdominal obesity (waist circumference >102 cm in men and >88 cm in women), (c) Triglycerides (≥150 mg/dl), (d) High density lipoprotein cholesterol (